Anti-coccidial effects of dietary chamomile against experimentally induced coccidiosis in broiler chicken - Sleman Said Mohammed Beski (Czech Journal of Animal Science, 2023)
A 4 × 2 factorial experiment was conducted to investigate the effect of dietary supplementation levels (0, 5 and 10 g/kg) of chamomile flower powder and a level (60 mg/kg) of salinomycin on performance and gut health of broiler chickens under coccidiosis challenge. A total of 320-day-old Ross 308 broilers were assigned to eight treatments of four replicates with 10 birds. Oral inoculation of the challenged groups with Eimeria tenella occurred on day 8. On day 10, disease challenge and additive level significantly (P = 0.003) interacted, decreasing the feed intake. Feed intake significantly (P ≤ 0.001) decreased in birds supplemented with 10 g/kg of chamomile. At 35 days, birds fed chamomile and anticoccidial significantly (P = 0.001) increased body weight (BW) and weight gain (WG). Disease challenge adversely influenced (P = 0.001) BW and WG. Additive level and disease challenge significantly (P = 0.001) interacted on feed conversion ratio (FCR). Anticoccidial and chamomile improved (P = 0.001) FCR of birds regardless of the rearing conditions. Significantly (P = 0.001) better FCR was observed in the unchallenged birds. The interaction of experimental factors was significant (P ≤ 0.04) on the relative weight of bursa. Disease challenge significantly (P = 0.005) increased the relative weight of liver whereas that of bursa decreased. Cholesterol (P = 0.002), albumin/globulin (P = 0.009), aspartate aminotransferase (AST) (P = 0.002) and alanine transaminase (ALT) (P = 0.001) significantly increased in challenged birds. The interaction of experimental factors was significant (P = 0.002) on villus length, crypt depth and villus height/crypt depth ratio (P = 0.001). Longer (P = 0.001) villi were found in anticoccidial and chamomile supplemented birds. Coccidiosis adversely (P = 0.001) influenced the jejunum morphology. Crypt depth decreased and villus height/crypt depth increased in chamomile offered birds (P = 0.001) regardless of the challenge conditions. Bursal morphology was significantly influenced by experimental factors. Dietary supplementation of chamomile had positive effects on broiler performance, immunity and intestinal morphology during exposure to the E. tenella parasite. Chamomile could be used as a potential natural anticoccidial in broiler nutrition.